The Potential of Lisosan G as a Possible Treatment for Glaucoma - Amato, Rosario; Rossino, Maria Grazia; Cammalleri, Maurizio; Timperio, Anna Maria; Fanelli, Giuseppina; Dal Monte, Massimo; Pucci, Laura; Casini, Giovanni (Frontiers in Pharmacology, 2021)
Lisosan G (LG), a fermented powder obtained from whole grains, is a nutritional supplement containing a variety of metabolites with documented antioxidant properties. We have recently demonstrated that orally administered LG protects diabetic rodent retinas from oxidative stress, inflammation, apoptosis, blood-retinal barrier disruption, and functional damage. Here, we investigated whether LG may exert protective effects in a model of glaucoma and measured the amounts of selected LG components that reach the retina after oral LG administration. Six-month-old DBA/2J mice were given an aqueous LG solution in place of drinking water for two months. During the two months of treatment with LG, the intraocular pressure (IOP) was monitored and the retinal ganglion cell (RGC) functional activity was recorded with pattern-electroretinography (PERG). At the end of the two-month period, the expression of oxidative stress and inflammatory markers was measured with qPCR, and RGC survival or macroglial activation were assessed with immunofluorescence. Alternatively, LG was administered by gavage and the concentrations of four of the main LG components (nicotinamide, gallic acid, 4-hydroxybenzoic acid, and quercetin) were measured in the retinas in the following 24h using mass spectrometry. LG treatment in DBA/2J mice did not influence IOP, but it affected RGC function since PERG amplitude was increased and PERG latency was decreased with respect to untreated DBA/2J mice. This improvement of RGC function was concomitant with a significant decrease of both oxidative stress and inflammation marker expression, of RGC loss, and of macroglial activation. All four LG metabolites were found in the retina, although with different proportions with respect to the amount in the dose of administered LG, and with different temporal profiles in the 24h following administration. These findings are consistent with a protective effect of LG in glaucoma that is likely to derive from its powerful antioxidant properties. The co-occurrence of different metabolites in LG may provide an added value to their beneficial effects and indicate LG as a basis for the potential treatment of a variety of retinal pathologies.